The Effect of Physicochemical Surface Treatment Methods on Bond Strength of Zirconia to Resin Cement: A Review of the Literature - Nojehdehyan, Hanieh; Moezzyzadeh, Maryam; Valizadeh Haghi, Haleh (Journal of Dental School, 2020)
Objective: Zirconium oxide has gained the spotlight during the recent years as a high strength ceramic material. However, despite its mechanical superiorities, it forms a weak bond with different synthetic substrates and tissues due to its neutral nature and resistance against chemical agents. Therefore, it is important to improve the bonding technique in order to prevent microleakage and increase retention and fracture resistance of the restoration. Literature Review: Since the discovery of zirconium oxide, several surface treatment methods have been evaluated to increase its bond strength to resin cement such as surface grinding with micro- abrasion, burs or abrasive papers, tribochemical silica coating, silicoating, glass micropearls, glaze- on technique, selective infiltration etching, hot etching and use of phosphate ester monomers. The mentioned techniques and related articles are reviewed and discussed in the present study. Conclusion: Despite extensive studies, no consensus has been reached about a specific treatment as the standard protocol for improving the bond strength of zirconia restorations.